PERMASALAHAN ANAK DALAM PENGUNGSIAN DI NANGGROE ACEH DARUSSALAM - Yanuar Farida Wismayanti (Politeknik Kesejahteraan Sosial, 2005)
(Children's Problems on the Refuge in Nanggroe Aceh Darussalam) - Restoration of post disaster area is a big agenda to recovery this area and to build life of system. Nature of disaster, earthquakes and tsunamis in Aceh (26/12/1004), this moment has attracted the attention from around the world to help and give support for peoples in disaster area. For that, some of different effort to recovery this area, involving the stakeholder, built a networking, develop and support a soladirity with a humanity of sense. A part of the big agenda of Aceh Recovery, it's very important to give a chance for children to be actor in this agenda, considering with the best for the children principles.